Asher Ghaffar, editor. History, Imperialism, Critique: New Essays in World Literature. Routledge, 2019. - Laura L. Dennis (Studies in 20th & 21st Century Literature, 2019)
Review of Asher Ghaffar, editor. History, Imperialism, Critique: New Essays in World Literature. Routledge, 2019. viii + 238 pp.
Keywords: Giambattista Vico; Timothy Brennan; World Literature